On the molecular mechanisms of mitotic kinase activation. Issue 11 (November 2012) - Bayliss, Richard; Fry, Andrew; Haq, Tamanna; Yeoh, Sharon
Abstract : During mitosis, human cells exhibit a peak of protein phosphorylation that alters the behaviour of a significant proportion of proteins, driving a dramatic transformation in the cell's shape, intracellular structures and biochemistry. These mitotic phosphorylation events are catalysed by several families of protein kinases, including Auroras, Cdks, Plks, Neks, Bubs, Haspin and Mps1/TTK. The catalytic activities of these kinases are activated by phosphorylation and through protein–protein interactions. In this review, we summarize the current state of knowledge of the structural basis of mitotic kinase activation mechanisms. This review aims to provide a clear and comprehensive primer on these mechanisms to a broad community of researchers, bringing together the common themes, and highlighting specific differences. Along the way, we have uncovered some features of these proteins that have previously gone unreported, and identified unexplored questions for future work. The dysregulation of mitotic kinases is associated with proliferative disorders such as cancer, and structural biology will continue to play a critical role in the development of chemical probes used to interrogate disease biology and applied to the treatment of patients.